Structural Analysis of One Block Compartment Building in Sentul Indah Residence Housing - Lutfi, Muhamad; Chayati, Nurul; Suali, Muhamad; Khaerul Insan, Muhammad; Syaiful, Syaiful; Muktadir, Redho (ASTONJADRO, 2024)
The rapid population growth in Indonesia has also increased the need for housing, according to data from the Ministry of Home Affairs through the Directorate General of Population and Civil Registry (Dukcapil) as of June 30, 2020, 268,583,016 people. The Ministry of PUPR said that housing needs in Indonesia are still high, to fulfill them not only from the state budget, but must work together with banks, developers, and local governments. Structural analysis carried out on a one-story compartment type residential building located in one Sentul Indah Residence (SIR) housing block in the Bogor Regency area is very important to ensure that building users are in a safe condition. The research was conducted by testing the concrete quality (fc) of existing columns, beams, and obtained concrete quality values sequentially of 30 MPa, 25 MPa, then modeling the existing structure using the ETABS application and obtained the results that the loads acting on the building and the combination of loads based on SNI were declared safe against the influence of external forces on the building by not finding structural elements that experienced over strenght (O/S). The results of the structural analysis plan based on SNI obtained the dimensions of a residential building with a size of 30 meters x 60 meters, reinforced concrete structure. The concrete material used is concrete with a quality (fc) of 30 Mpa. Column dimensions 20x20 cm with 2D12 main reinforcement and shear reinforcement and shear reinforcement diameter 10-70, beam dimensions 15x20 cm with 2D12 main reinforcement and shear reinforcement diameter 10-100.